PELATIHAN DAN PENDAMPINGAN PENGGUNAAN SOFTWARE STUDI ISLAM BAGI MUBALLIGH PIMPINAN DAERAH MUHAMMADIYAH KABUPATEN MALANG - Jamal, Jamal; Muslikhati, Muslikhati; Yusuf, Muhammad (Bulletin of Community Service and Development, 2022)
Purpose of the study: The purpose of this activity is to improve the ability of muballigh using Islamic study software for the benefit of da'wah so that they can find references easily, quickly and validly in accordance with the applicable rules in Islamic sciences without having to open the literature manually which of course takes time. Islamic studies software is also able to help the muballigh answer questions from the community regarding certain laws in which there are ikhtilaf of the Ulama' Methodology: The implementation method that refers to the program situation analysis that is mutually agreed upon is discussion, socialization, interactive dialogue, and the practice using software of Islamic studies. Main Findings: Muballigh at PDM Malang who initially did not have the ability and experienced difficulties when tracing literacy and using Islamic studies software had an understanding regarding the use of this application. Applications of this study: This service is useful for Muballigh in PDM Malang in the use of Islamic studies software. Novelty/Originality of this study: The preacher at PDM Malang is able to use Islamic studies software.